STRATEGI DESAIN PRODUK DALAM MENGOPTIMALISASI NICHE MARKET PROPERTY VILA DAN RUMAH - Daniswara Daniswara (Jurnal Manajemen dan Bisnis, 2015)
The growth rate of the property houses and villas in Bali growing from year to year.Bali is one of the famous tourism object in the world led to many local and foreign tourists whocome to Bali to visit, vacation or for foreign tourists investasi.Banyaknya idolized and lovedthe beautiful island of Bali as make them want to keep coming to Bali and want to have adwelling place in Bali. This leads to Bali increasingly popular and very promising future forthe property business. Cv. Freeline Immanuel and PT. Niki Build Prosperity (NBS) is aproperty developer with a careful look at the potential of this Niche Market. With so manycompetitors PT. NBS and Cv. Freeline Immanuel must create a design that is unique anddifficult to imitate by competitors. This must be done in order to optimize the Niche Market tobe able to win the competition. Based on the above phenomenon worth doing research with thetitle of product design strategies to optimize Niche Market property.To achieve the goal of this research is to know strategies to optimize product designsNiche Market property, then it is done collecting data obtained through interviews withinformants in this study. Data analysis was performed by organizing the data, describe thedata, perform sistesa, compiled into a pattern, select the data that is important and that will betaken and studied and make conclusions.Based on the results of the discussions that have been described can be concluded thatthe Product Design Strategies for optimizing Niche Market Property implemented by PT. NikiBuild Prosperity and CV. Freeline Emmanuel is with flexible design, artistic and uniquedesign, interior design and beautiful exterior and fused, and the design of environmentallyfriendly green architecture.Keyword: Product Desain Strategy, Property